(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Since times immemorial women have been oppressed in patriarchal machinery.This steadydecline in the status of women can be traced back to the post-rigvedic period. Across culture, religion,class and caste, the attitude towards women is same in the whole world. Suppression of women is one ofthe important issues even today attracting the attention of not only sociologists and economists but alsoof writers and Directors.This research examines the representation and revolt of women in Henrik Ibsen’s A Doll’s Home (1879).Ibsen, one of the greatest dramatists of all time, is widely regarded as the forefather of the contemporarytheatre genre and as a staunch advocate for gender equality. A self-described humanist rather than afeminist, he never uses the term feminist to describe himself. Moreover, several of his plays have strongfeminist leanings. This presentation will use Simone de Beauvoir’s notion of woman as the Other as aspringboard to argue against all societal constraints, particularly the institution of marriage. Ibsen’stheory drives the exploration of individuality and humanity as important societal challenges. Since theylimit the characters’ ability to be themselves and behave freely, all societal norms and expectations arethe adversary of every person. More specifically, Ibsen deepens this perspective on women, whoseautonomy and independence are subsumed by a male-dominated society. Nora is a doll of a lady, wife,and mother. She is a victim of patriarchal society’s unseen hands and forces. Ibsen decries theoppression of women and the prevalence of male authority in today’s society.